The Performance of Collective Investment Contract of Stock Mutual Fund In Indonesia - Victor Siagian (Business and Entrepreneurial Review, 2006)
The are two kinds of stock mutual fund, namely company and collective investment contract of stock mutual fund. Three aspects must be considered by investor in selecting stock mutualfund, (1) how much rate of return, (2) is rate of risk and (3) is performance or professionality of porlfolio management of stock mutual fund. To analyze the performance of stock mutual fund, especially collective investment contract of stock mutual fund in Indonesia, is the objective of this study. Based on theoretical and empirical review, it is able to design hypothesis. Data collections in this study covering IHSG, BI rate and Net Asset Value (NAV) of stock mutual funds. Alfa Jensen's model was used to evaluate the performance of collective investment contract of stock mutual fund. The finding of this study shows that only two of six of stock mutual fund which are observed as sample, have outperform toward market performance and the others are underperfoms condition.